1989
DOI: 10.1017/s0950268800029654
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Legionellaceae at a hot spring spa: a prospective clinical and serological study

Abstract: SUMMARYFollowing the occurrence of five cases of Legionnaires' disease among patients and therapists at a French hot spring spa, a series of cleansing procedures and an epidemiological study were undertaken. During a 3-month period, the spring water was repeatedly sampled. Serum samples were taken from 689 randomly selected patients, 230 therapists, 134 administrative staff and a control group of 904 blood donors.Legionellaceae were present in the spring water at concentrations of 103-105 colony forming units/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 4 publications
3
48
0
Order By: Relevance
“…However, strains of Legionella pneumophila other than serogroup-1 have also been reported to be the causative agents of Legionella pneumonia, the sources of infection with which seem to be the waters of hot spring spas (6,15). The reason for this difference in causative agents is considered to be differences in bacterial distribution in the environment (3,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…However, strains of Legionella pneumophila other than serogroup-1 have also been reported to be the causative agents of Legionella pneumonia, the sources of infection with which seem to be the waters of hot spring spas (6,15). The reason for this difference in causative agents is considered to be differences in bacterial distribution in the environment (3,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…They include outbreaks associated with a hot spa [6], fountains [7], a grocery mist machine [8], hot water systems [9], whirlpool baths on a cruise ship [10] as well as evaporative condensers and cooling towers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Yabuuchi et al investigated the distribution of Legionella in Japanese hot spring spa water and reported that 84 (62%) of 135 hot springs investigated harbored the organism (21). Serological studies from France (22) and Portugal (23) showed that Legionella antibody titers were increased in persons whohad been exposed to hot spring spa water contaminated with the bacteria. Our result supports the circumstantial evidence that the patient was infected with L. pneumophila serogroup 6 and developed severe pneumoniafollowing aspiration of the hot spring spa water.…”
Section: Discussionmentioning
confidence: 99%